METODE DEMONSTRASI EKSTRAKURIKULER DRUM BAND SMPN 2 PADANG: STUDI TERHADAP PENGALAMAN SUBJEKTIF PELATIH DALAM MENENTUKAN METODE - Ahmad Fauzi Nasution; Agung Dwi Putra (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to understand the coach’s subjective experience in the process of developing awareness and forming beliefs regarding the use of the demonstration method, as well as to reveal the reasons behind the coach’s decision to choose this method as the main approach in drum band extracurricular activities at SMP Negeri 2 Padang. This study employed a qualitative approach with a phenomenological method. Data were collected through document analysis, observation, and in-depth interviews with the coach as the main informant. Data analysis was conducted through organizing and interpreting themes that emerged from the informant’s experiences. The results show that the use of the demonstration method is formed through a gradual experiential process. Past experiences, direct practice during training, and observations of students’ development shape the informant’s awareness in understanding the training process. This awareness then develops into a belief in using the demonstration method. In addition, the demonstration method is chosen because it helps students understand the material more easily, increases their confidence to try, and facilitates the evaluation process during training. Students’ success in performing the material becomes an experience that further strengthens the informant’s belief in the method. Thus, the selection of the demonstration method is the result of the informant’s subjective experience and understanding that continuously develop throughout the training practice.